Recent Publications (Quarterly Journal of Economics, 1968)
Recent Publications Get access The Quarterly Journal of Economics, Volume 82, Issue 3, August 1968, Pages 528–535, https://doi.org/10.1093/qje/82.3.528 Published: 01 August 1968